Impact of Value Added Tax on Economic Growth of Nigeria (UNIZIK Journal of Marketing, 2024)
The bond between Nigeria's economic growth and value added tax was empirically investigated in this study. The Central Bank of Nigeria (CBN) provided time series data covering the gross domestic product (GDP), total revenue (TR), and value added tax (VAT) revenue from 1994 to 2022. Both descriptive statistical methods and simple regression analysis were used to analyze the data. As stand-ins for Nigeria's economic growth, TR, and GDP were the dependent variables, and VAT was the independent variable. Descriptive statistics reveal significant fluctuations in these variables, reflecting diverse economic conditions and policy changes. Strong positive correlations were found among GDP, TR, and VAT emerging as a significant predictor of VAT in regression analysis. The findings indicate that economic growth, as captured by GDP, is a crucial driver of VAT revenue, highlighting the importance of policies aimed at stimulating economic growth while considering the broader fiscal context for balanced and sustainable development.
Keywords: Value Added Tax; Taxes; Total (Federal Government) Revenue; Gross Domestic Product; Nigeria